Changeable factors for diabetes mellitus type II patients and compare it with healthy control (Journal of Advances and Scholarly Researches in Allied Education, 2024)
A study has been analysed “Changeable factors for diabetes mellitus type II patients and compare it with healthy control.” A random sample total 150 well-informed, informed consented subjects of either male and female 35-70 years of age group has been selected from Bihar. 100 patients suffering from diabetes mellitus type II were placed in group 1 (serving as cases) and fifty (50) apparently healthy individuals with matched age were place in group 2 (serving as a healthy control). The number of the disease population is believed to be approx. 70-90 per% of apparently healthy Indians have under vitamin D level across all the regions and age groups. In the present, diabetic cases had 19.09±5.34 ng/ml of serum vitamin D level. Healthy control subjects had 26.55±3.61 ng/ml of serum. The results been showed that 53% male and 47% female participants among cases. 40% male and 60% female participants among healthy control. Diabetes mellitus of patients, 17 cases were under good control, 28 were under fair control and 55 were under poor control. Diabetic cases had 19.09±5.34 ng/ml of serum vitamin D level. Healthy control subjects had 26.55±3.61 ng/ml of serum vitamin D.